Robust cost modelling for ink-jetted pharmaceuticals (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: With the ability of producing on-demand, personalized and complex products, Additive Manufacturing (AM) promises a pathway towards more precise drugs while at the same time facilitating a reorientation towards smaller-batch size and on-demand manufacturing. However, research addressing the economic impact of AM on pharmaceutical manufacturing has so far been very limited. In particular, there is a dearth of empirical investigations into manufacturing costs of additively deposited drugs despite an urgent need within the pharmaceutical industry to understand the cost relationships embodied by the technology prior to its adoption.Materials and Methods: Based the application of existing cost models within the medical device domain, we develop a robust cost model for ink-jetted solid dosage forms by incorporating factors of batch size, necessary ancillary process elements, process failure, product rejection and material waste streams. In an experimental approach involving the material jetting system Dimatix DMP 2830, we investigate the fabrication of Ropinirole, a medication developed to treat Parkinson’s disease.Results and Discussion: The experimental data provides detailed insight into the relationships between technological parameters and cost characteristics, several of which take the form of trade-offs. Our results show that increasing the batch size reduces well-structured unit costs but also leads to increasing costs relating to risk and build failure. AM systems are able to deposit a large variety of tablets and there are thus very limited costs associated with changeovers and customization.Conclusion: We perceive possible applications for AM in the manufacture of orphan drugs targeting small patient populations - which is associated with a high profit potential. However, our experimental investigation into manufacturing cost demonstrates that there are still hurdles to overcome on the journey to commercial-scale manufacturing, including scale-up, process stability, automation, in-process monitoring quality control, etc.